Vitamins and coenzymes. - McCormick, Donald B. (Donald Bruce); Suttie, J. W. (John Weston), 1934-; Wagner, Conrad (Methods in enzymology, 1997)
This volume of Methods in Enzymology and its companion volumes 280, 281, and 282 present new methods and their modifications developed in the past decade plus the more recently acquired knowledge on the functional and metabolic aspects of vitamins and coenzymes. They represent the only in-depth treatment dealing with methods related to vitamins and coenzymes, and contain methods that have never been grouped together before. Key Features * This volume and its companion Volumes 280, 281, and 282 provide * A collation of the most recent and useful methods for the identfication, preparation, and quantification of vitamins and coenzymes * Details on physical, chemical, and biological properties of vitamins and coenzymes * Chemical and biological syntheses of vitamins, coenzymes, and their analogs * Aspects of transport and metabolism of vitamins and coenzymes.